You will never again be a Chilean like the others: From diaspora to diasporic practices among Chilean refugees returning from exile (Journal of Comparative Social Work, 2011)
In this paper we focus on repatriation of refugees who came to Norway after the coup d'état in Chile in 1973. The Chilean refugees formed part of a diaspora during exile. The authors’ concern is the returnees' relationship with the diaspora upon return. The purpose of the article is to discuss whether the notion of diaspora may contribute to an understanding of the situation of the returnees. Diaspora is widely used in migration studies, although the concept is not particularly related to studies on refugees and their return. The article is based on interviews with Chilean returnees from Norwegian exile. The authors argue that their situation may be best understood as one of continued diasporic identity and diasporic consciousness.